Ulcers Legs and Lymphedema - Abbade, Luciana Patrícia Fernandes [UNESP]; Miot, Hélio Amante [UNESP] (Springer Nature, 2023)
Leg ulcers are of major concern in public health because of their high prevalence (especially among older people), chronicity, economic burden, and impact on quality of life. Besides the need for primary prevention in susceptible groups, adequate etiologic diagnosis and a multispecialty approach can lead to successful treatment. Similarly, chronic lymphedema is a limiting disorder that predisposes to recurrent soft skin infection, leg ulcers, and malignancy. In this chapter, we discuss clinical patterns, diagnostic procedures, and management of the main types of leg ulcers and lymphedema.
Keywords: Hypertensive ischemic ulcer; Leg ulcer; Lower extremity ulcer; Lymphedema; Martorell’s ulcer; Varicose ulcer; Venous insufficiency